Shaping Soil Properties and Yield of Cereals Using Cover Crops under Conservation Soil Tillage - Wilczewski, Edward; Jug, Irena; Szpunar-Krok, Ewa; Staniak, Mariola; Jug, Danijel (Agronomy (Basel), 2024)
The aim of this review was to collect current results on the effect of different plants grown as winter and summer cover crops (CC) on the physical, chemical, and biological properties of soil and on the yield of cereal crops grown in a site with CC, using conservation soil tillage. The analyzed studies indicate that CC usually have a positive impact on the physical and biological properties of the soil. Regardless of the plant species used as CC, we can expect an increase in the number of soil microorganisms and an improvement in the activity of soil enzymes. This effect is particularly beneficial in the case of reduced tillage systems. Mixing CC biomass with the topsoil loosens compacted soils and, in the case of light, sandy soils, increasing the capacity of the sorption complex. The size and composition of CC biomass and weather conditions during the vegetation period and during the covering of the soil with plant biomass are of great importance for improving the chemical properties of the soil. A beneficial effect of CC, especially legumes, on the content of the mineral nitrogen in the topsoil is usually observed. Sometimes, an increase in the content of available forms of potassium (K) and/or phosphorus (P) is also achieved. The effect of CC on the content of soil organic carbon (C), total nitrogen (N), or soil pH is less common. CC used in reduced tillage systems can significantly improve the yield and quality of cereal grain, especially when legumes are used as CC in low-fertility soil conditions and at low fertilization levels. However, non-legumes can also play a very positive role in shaping soil properties and improving cereal yield.